The Korean economy at the crossroads - Tcha, MoonJoong; Suh, Chung-Sok (London ; New York : RoutledgeCurzon, 2003)
Until 1997, Korea was widely seen in economic and financial circles as something of a miracle. The financial crisis did much to set its economy back, but by 2001 it was still the 13th largest economy in terms of GDP in the world. This collection charts the well documented causes of the crisis, its response and recovery from it.
Includes bibliographical references and index.
rpm 22/08/16
Loans
Keywords: Finance; Korea (South) -- Economic conditions -- 1960-1988.; Finance -- Korea (South) -- History -- 20th century; Korea (South)